Structural and synthetic investigations of South African marine natural products - Beukes, Denzil Ronwynne (Rhodes University, Faculty of Science, Department of Chemistry, 2000)
A chemical investigation of six different marine invertebrates, collected along the South African coastline, resulted in the isolation and structural elucidation of fifteen previously undescribed secondary metabolites along with seven known compounds. The structures of the new metabolites were determined by a combination of spectroscopic and chemical methods. The endemic false limpet Siphonaria capensis was shown to contain two unusual polypropionate metabolites capensinone (162) and capensifuranone (163) as well as 2,4,6,8-tetramethyl-2-undecenoic acid (164) and the known polypropionates (E)- and (Z)siphonarienfuranone (149 and 161). Capensinone is the first example of a marine polypropionate containing a cyc1opentenone moiety. An investigation of the endemic South African soft coral Pieterfaurea unilobata yielded six new, highly oxygenated, pregnadiene sterols (180-185) and the known metabolite (169). Compounds 180-185 are the first pregnadienes obtained from the marine environment containing a C-7 substituent. An alternative procedure for the quick assignment of the absolute configuration at C-3 in this series of compounds was proposed. A companson of the pyrroloiminoquinone alkaloids of three undescribed l'}trunculid sponges resulted in the isolation of 3-dihÂ¥drodiscorhabdin C (243), 3-dihydrodiscorhabdin B (244), discorhabdin H (197) and the previously reported alkaloids discorhabdin A (189) and discorhabdin D (192). While all three sponges were found to be morphologically different they all contained discorhabdin A as the major metabolite and discorhabdin H as one of their minor metabolites. It was found that a feature common to most of the South African latrunculid sponges is the reduction of the C-3 carbonyl gr,o up in some of the minor metabolites. The indole alkaloids, dilemmaones A-C (261-263), containing an unusual cyc1opentanone-indole skeleton, were isolated in trace amounts by bioassay guided fractionation of an extract obtained from a mixed collection of sponges collected near Cape Town. In an attempt to acquire more of these novel compounds for further investigation of their biological activity, several synthetic strategies towards their total synthesis were explored. A key feature of these approaches was the exploitation of the regioselective Gassman's artha-alkylation procedure for the introduction of an aromatic methyl substituent.
Keywords: Natural products -- South Africa; Marine invertebrates -- South Africa; Marine metabolites -- South Africa